The British and university reform policy in Germany, 1945-49 - Phillips, D; Phillips, D. G. (1984)
﻿ This study traces the development of British policy towards the universities and other Hochschulen in the British Zone of Germany during 1945-49. It starts by describing in outline the salient features of the German university against the background of the criticisms levelled against it by those in Britain who had been working on the problems of dealing with a defeated Germany. Chapter Two describes the war-time planning; the allied conferences and statements, the influence of Vansittart and Morgenthau, the role of Professor E.R. Dodds and the émigrés and others, and the military government handbooks and directives. There follows a description of the university institutions of the Zone and their students. Chapter Four addresses the question of British control and the universities, focussing on the military governors, chains of communication, Education Branch, the Educational Adviser,;.and, more particularly, the University Officers and their duties. It considers also the 'dereservation' of education, denazification, democratisation, and re-education. Chapter Five describes the report of the AUT delegation to Germany of January 1947: this is analysed in full and seen in its relation to the setting-up of the Studienausschuß für Hochschulreform, the subject of the succeeding chapter. The work of the Studienausschuß is described, and the genesis of the Blaues Gutachten of 1948 is reconstructed and its findings are related to British policy. The part played by Lord Lindsay in the work of the Commission is considered in detail. Chapter Seven examines the impact of the Gutachten on the universities of Germany and a final chapter reaches conclusions about the nature of British policy towards higher education in the Zone. The footnotes provide a guide to the unpublished material; the bibliography lists published sources, and a separate volume of appendices provides the essential documentation.